Identification and chemical characterization of N-acyl-homoserine lactone quorum sensing signals across sponge species and time. Issue 2 (18th December 2017) - Britstein, Maya; Saurav, Kumar; Teta, Roberta; Sala, Gerardo Della; Bar-Shalom, Rinat; Stoppelli, Nausicaa; Zoccarato, Luca; Costantino, Valeria; Steindler, Laura
Abstract: Marine sponges form symbiotic relationships with complex microbial communities, yet little is known about the mechanisms by which these microbes regulate their behavior through gene expression. Many bacterial communities regulate gene expression using chemical signaling termed quorum sensing. While a few previous studies have shown presence of N -acyl-homoserine lactone (AHL)-based quorum sensing in marine sponges, the chemical identity of AHL signals has been published for only two sponge species. In this study, we screened for AHLs in extracts from 15 sponge species (109 specimens in total) from the Mediterranean and Red Sea, using a wide-range AHL biosensor. This is the first time that AHL presence was examined over time in sponges. We detected the presence of AHL in 46% of the sponge species and found that AHL signals differ for certain sponge species in time and across sponge individuals. Furthermore, for the Mediterranean sponge species Sarcotragus fasciculatus, we identified 14 different AHLs. The constant presence of specific AHL molecules in all specimens, together with varying signaling molecules between the different specimens, makes Sa. fasciculatus a good model to further investigate the function of quorum sensing in sponge-associated bacteria. This study extends the knowledge of AHL-based quorum sensing in marine sponges. Abstract : Bacterial signal molecules (AHLs) are common in sponges, yet do not relate to abundance of microbial symbionts. A single sponge can harbor >10 different AHLs.